PHYSICO-CHEMICAL VALUE AND HYPOGLYCEMIC EFFECT OF INDUSTRIAL-GRADE ETHANOLIC EXTRACT OF PIGEON PEA (Cajanus cajan) LEAVES AND GINGER (Zingiber officinale var. amarum) - Wresdiyati, Tutik; Alfarisi, Hamzah; Putri, Anisya Saeila; Abidah, Puri Adzrok; Darawati, Made; Aziz, Sandra; Sadiah, Siti; Astawan, Made; Santoso, Koekoeh (Jurnal Kedokteran Hewan, 2024)
This study aimed to analyze flavonoid and 6-gingerol content and to test the hypoglycemic effects of industrial-grade Cajanus cajan (pigeon pea) leaf and Zingiber officinale rhizome (ginger) extracts on hyperglycemic rats. Extraction utilized maceration with 70% alcohol at PT. Insular Multi Natural. Extracts were characterized and analyzed for flavonoids and 6-gingerol content. Hypoglycemic activity was assessed using the oral glucose tolerance test (OGTT) on rats with induced hyperglycemia via 90% sucrose solution. The results indicated higher flavonoid content in C. cajan leaf extract (4090.09338.23 mg/100 g) compared to Z. officinale extract (622.74203.39 mg/100 g), while gingerol content in Z. officinale extract was 701.524.42 mg/100 g. This study concluded that combination of industrial-grade pigeon pea leaves extract and ginger extract reduce the level of blood glucose in hyperglycemic model rats at all combination dose (150:150, 200:100, and 100:200 mg/kg BW). The combination dose of 200:100 mg/kg BW showed the best blood glucose level profile.